PEMBUATAN ALAT PENGOLAHAN AIR DALAM RANGKA MENGATASI PENCEMARAN BESI DALAM AIR SUMUR - Dian Wuri Astuti, Desto Arisandi (Universitas Respati Yogyakarta, 2017)
Making of water instalation was conducted in order to solve the problem of pollution of domestic drinking water. Ngemplak Seneng vilage located in the districts of Manisrenggo Klaten of Central Java. Ngemplak Seneng is one of the Merapi disaster prone villages belonging to the densely populated with low health levels. The presence of iron in the water supply system in the village of Ngemplak Seneng especially in RT 19 Dukuh III which exceeds a set threshold. For drinking water, the concentration of iron is limited to maximum of 0.3 mg/L according to the Indonesian Health Ministry regulation 492 / Menkes / PER / IV / 2010. For that, it needs the oxidation process by means of aeration. The problem of iron in the Ngemplak Seneng likely due to their high iron content in ash and volcanic sand carried the rest of the Merapi eruption into the soil. The results of examination were obtained reduction of iron levels more than 80%. Water instalation was made in two different places because high public demand for clean water. Keywords: iron, wells water, oxidation-aeration